2014
DOI: 10.9790/3008-09320610
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Echinococcus granulose in Samples of Iraqi Patients

Abstract: Abstract:Background Result: Most of the CE patients(60) patients were found to be infected with hydatid cyst of eitherG4 26(43%),G1/G/G3 18(30%), G5 12(20%),G6/G7 4(7%). And the study the association of genotypes and organ ,our results show In the liver (20%) G1/G/G3 ,(27%)G4 ,(7%) G5 ,(20%) G6/G7. Lung (7%) G1/G/G3,(10%)G4,Liver and lung (3%) G1/G/G3 andG4 ,finally liver ,lung and spleen (3%) G1/G/G3. Conclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Highest prevalence of CE was in the liver and the lungs, this is in agreement with the results of Ibrahim (2010), Hama (2013), Sargali and Mero (2013), AL-Bosely (2014), Mero et al (2014). This is because the liver act as the first filter for larval infection and the lungs as the second filter, and the oncosphere adopt the portal vein route and primarily negotiate hepatic and pulmonary filtering system sequentially before any other peripheral organ is involved (Kebede et al, 2009;Khalf et al, 2014;Mero et al, 2014;and Temam et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Highest prevalence of CE was in the liver and the lungs, this is in agreement with the results of Ibrahim (2010), Hama (2013), Sargali and Mero (2013), AL-Bosely (2014), Mero et al (2014). This is because the liver act as the first filter for larval infection and the lungs as the second filter, and the oncosphere adopt the portal vein route and primarily negotiate hepatic and pulmonary filtering system sequentially before any other peripheral organ is involved (Kebede et al, 2009;Khalf et al, 2014;Mero et al, 2014;and Temam et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…The higher rate of liver and both (liver and lungs) involvement because liver act as the first filter for larval infection and the lungs act as the second filter, furthermore the liver possess the first great capillaries sites encountered by migrating the Echinococcus oncosphere (hexacanth embryo) which adopt the portal vein route and primarily negotiate hepatic and pulmonary filtering system sequentially before any other peripheral organ is involved (Kebede et al, 2009;Khalf et al, 2014;Mero et al, 2014 andQingling et al, 2014). The liver of sheep and goats were found to be more commonly infected with hydatid cysts than the lungs is in agreement with the previous findings of Saeed et al( 2000); Yildiz and Gurcan (2003); Haridy et al(2006); Kamhawi et al(2009);Saida and Nouraddin (2011);Jarjees and Al-Bakri(2012), and Khalf et al(2014). In contrast Sargali and Mero (2013) found 56.1% of HC in lungs and 36.25% and 7.66% in liver alone and both liver and lungs, and in goats, 67.31, 25.5 and 7.2% of HC were ISSN: 2410-7549 found in lungs, liver and both liver and lungs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present works represented that, most of the isolates analyzed belonged to the G1 genotyping (sheep strain), and shown that this strain is actively transmitted throughout the Kurdistan region and surrounding countries [21][22][23], and the sheep play a significant role in human transmission cycle and the and the absence of G4, G6, and G7 genotype in this investigation is probably explained by the fact that in Kurdistan region, these genotype are specific to the species that were not slaughtered in slaughter house, like baffle, horse and pigs. The result disagreement with [24], who observed that in Iraq, the majority of CE patients (60) were infected with hydatid cysts of either G4 (43⁒), G5 (20⁒), and G6/G7 (7⁒) and [25] reported that, 38 isolates were sequenced by using polymerase chain reaction to amplify mitochondrial COX1 gene in the south-east of Iran and The genotype G1 was most prevalent in sheep (86.7%), cattle (80%), camels (44.4%), and goats (100%). Furthermore, [26] revealed that, of the 20 goat samples tested, 17 isolates (85%) were of the sheep strain's G1 genotype and the other three isolates (15%) were of the G6 genotype.…”
Section: -Discussionmentioning
confidence: 84%